Zgodnje raziskovanje vakuuma v Srednji Evropi in med Slovenci - Južnič, Stanislav (Vakuumist, 2005)
The early development of vacuum enterprises Leybold and Heraeus in German part of the Middle Europe is discussed. Their success followed the most important achievements in the research of the vacuum theory of the border of Slovene. Middle European lands that Cauchy accomplished in Gorica in the years 1836-1838. By using French and Italian archive sources we describe Cauchy's life and work in Gorica for the first time in historiography. We discuss the main Cauchy's scientific collaborators in Prague, Vienna, Graz, Ljubljana and Gorica. Cauchy's work considerably influenced the later deveopment of Middle European vacuum research from Balzers to modern Slovene inventions.
Keywords: Carniola; Cauchy, Augustin Louis, 1789-1857; Habsburg Monarchy; habsburška monarhija; Kranjska; vakuumska tehnika; zgodovinski pregledi